2017
DOI: 10.1016/j.matlet.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation of Cu single crystals containing an elliptic cylindrical void

Abstract: Molecular dynamics simulations are performed to study the plastic deformation of Cu single crystals containing an elliptic cylindrical void. The effects of initial void geometry including void ellipticity and void orientation angle on plastic deformation are examined by considering the stress-strain response, dislocation nucleation from the void surface, and porosity/void cross-sectional shape evolution. It is found that (i) the initial void geometry plays an important role and (ii) the growth of voids with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Soon after, Tang et al 21 revealed the dislocation mechanism during the void growth and demonstrated the void size effect on the critical stress to initiate plasticity in both face-centered cubic (FCC) and body-centered cubic (BCC) metals. Temperature sensitivity, 22 different stress states and strain rates, 23 void geometry, 24 void in nanowire, 25 and array distribution of void 26 were studied to elucidate the void related plastic deformation or failure mechanism. However, most of the above studies are based on the assumption that there are no other defects around the preexisting voids initially.…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, Tang et al 21 revealed the dislocation mechanism during the void growth and demonstrated the void size effect on the critical stress to initiate plasticity in both face-centered cubic (FCC) and body-centered cubic (BCC) metals. Temperature sensitivity, 22 different stress states and strain rates, 23 void geometry, 24 void in nanowire, 25 and array distribution of void 26 were studied to elucidate the void related plastic deformation or failure mechanism. However, most of the above studies are based on the assumption that there are no other defects around the preexisting voids initially.…”
Section: Introductionmentioning
confidence: 99%
“…Prior atomistic studies revealed that the nanovoid growth process is affected by many factors, including, but not limited to, strain rate [9], temperature [10], initial porosity [11], initial void shape [12], and crystallographic orientations [13,14,15]. Compared with face-centered cubic (FCC) [1,10,12] and body-centered cubic (BCC) [9,2,11] systems, there exist much fewer studies of nanvoids in metals with a hexagonal close-packed (HCP) lattice, in part due to a lack of reliable interatomic potential and more complicated slip/twinning systems in the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with face-centered cubic (FCC) [1,10,12] and body-centered cubic (BCC) [9,2,11] systems, there exist much fewer studies of nanvoids in metals with a hexagonal close-packed (HCP) lattice, in part due to a lack of reliable interatomic potential and more complicated slip/twinning systems in the latter. Particularly for HCP Mg, the lightest and the third most abundant element in the Earth's crust among all metals, most atomistic simulations in the literature concerned nanocracks [16,17,18,19]; to the best of our knowledge, only a few MD and atomistic-based multiscale studies have been devoted to nanovoids [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, nanotwinned small‐sized metallic systems, for example, nanopillars and nanotubes, with either parallel or fivefold CTBs, remain relatively lightly explored . Compared with 3D nanocrystals, 1D nanopillars/nanotubes with free surfaces attain additional geometric features including outer/inner diameter and cross‐sectional shape which, along with the CTB spacing, may significantly alter their mechanical properties . On the other hand, deformation may annihilate nanotwins and increase the CTB spacing .…”
mentioning
confidence: 99%